2020
DOI: 10.3390/nano10061138
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rotating Cylinder toward Mixed Convection inside a Wavy Heated Cavity via Two-Phase Nanofluid Concept

Abstract: The mixed convection two-phase flow and heat transfer of nanofluids were addressed within a wavy wall enclosure containing a solid rotating cylinder. The annulus area between the cylinder and the enclosure was filled with water-alumina nanofluid. Buongiorno’s model was applied to assess the local distribution of nanoparticles in the host fluid. The governing equations for the mass conservation of nanofluid, nanoparticles, and energy conservation in the nanofluid and the rotating cylinder were carried out and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…A similar trend is noticed for Nu avg at the upper wall (see Figure 10b), though Nu avg at the upper wall is comparatively less than Nu avg at the circular heater. Such result is quite common in the study of mixed convection in cavities and reported by various authors (See for instance [9]). Table 4 depicts the percentage change in Nu avg as the percentage of the volume fraction of nanoparticles augments at Ri = 1.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…A similar trend is noticed for Nu avg at the upper wall (see Figure 10b), though Nu avg at the upper wall is comparatively less than Nu avg at the circular heater. Such result is quite common in the study of mixed convection in cavities and reported by various authors (See for instance [9]). Table 4 depicts the percentage change in Nu avg as the percentage of the volume fraction of nanoparticles augments at Ri = 1.…”
Section: Resultssupporting
confidence: 67%
“…They also reported a decrease in the average Nusselt number with an increase in the heater length. Basak, et al [8], Alsabery, et al [9], Li, et al [10], and Alsabery, et al [11] used different thermal boundary conditions and found an upsurge in the intensity of vortices with rising Grashof number. The local Nusselt number reveals non-monotonic features on the heated surface for higher Darcy and Prandtl numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Combined convection flow across a heated wavy enclosure filled with Al 2 O 3 –H 2 O nanoliquid and containing a rotating cylinder were examined numerically by Alsabery et al . 14 , They found that in both directions of the rotating cylinder, the mean Nusselt number increased as Richardson's numbers increased. Hashim et al .…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue consists of twelve articles dedicated to nanofluid properties [ 1 ], the influence of nanoparticles on properties of other materials [ 2 , 3 , 4 ], as well as the possibility to enhance the heat transfer in different engineering devices using nanofluids, including the cooling of heat-generating elements in electronic devices [ 5 , 6 , 7 , 8 ], minichannel [ 9 ] and microchannel [ 10 ] optimization, and heat exchangers [ 11 , 12 ]. The objective of this Special Issue is to demonstrate the recent studies on nanoparticles and nanofluid applications in material treatment and engineering device optimization, which could be very useful for various specialists in mechanical and chemical engineering, physics, and mathematics.…”
mentioning
confidence: 99%
“…The analysis has shown that the multi-channel system can increase the heat transfer rate, while an addition of nanoparticles also illustrates the energy transport enhancement. Alsabery et al [ 11 ] have computationally examined the influence of a rotated inner cylinder on convective energy transport in a wavy differentially heated chamber filled with alumina-water nanofluid. Using the Buongiorno nanofluid model with effects of Brownian diffusion and thermophoresis, the authors have shown a possible energy transference enhancement with nanoparticle concentration.…”
mentioning
confidence: 99%